Effects of drought stress simulated by peg on seed germination of two ecotypes of ceratoides arborescens (Mongolian Journal of Agricultural Sciences, 2017)
Ceratoides arborescens is widely distributed in arid area of Inner Mongolia. They are fine sand binding plants, and the main feed of livestock in arid desert area in the dry season. Under drought stress, seed germination and seedling root growth is very important to the survival and development of plant seedlings. Therefore our main objective of this study was to determine the effects of drought stress on seed germination and seedling growth of two ecotypes, Wu and Kerqin, of Ceratoides arborescens. The effects of drought stress on seed germination under PEG treatment and germination recovery under optimal conditions after presoaking with PEG solution were studied in a series of laboratory tests. The germination and radical growth of the two ecotype Wu and Kerqin of Ceratoides arborescens were studied to different degrees of inhibition with reduced osmotic potential of a series of PEG solutions. However, slight drought stress promoted the seed germination of the two ecotype Wu and Kerqin of Ceratoides arborescens and improved the germination index of the two ecotypes, simulating the radical growth. The lowest osmotic potential for germination was -2.1MPa for Kerqin and -1.8MPa for Wu. The result shows that the drought resistance of seed germination of Kerqin was stronger than that of Wu.Under optimal conditions, the seeds presoaked with PEG solution recovered their germination after drought stress was relived. The seeds presoaked longer, suffered greater from drought stress and germination was suppressed completely. The radical length of the primary root of the two species had no significant difference between the CK after presoaking with PEG solution in 3d，and then decreased significantly with the increase of days of presoaking.